IMPLEMENTATION OF THE ICE-BREAKING METHOD TO INCREASE FOURTH-GRADE STUDENT UNDERSTANDING OF THE MATERIAL “TELLING TIME” IN AL – A’RAF BILINGUAL ELEMENTARY SCHOOL - Maida Prihatini; Nuzulul Isna (Yayasan Nusantara Hasana Berdikari, 2023)
Ice Breaking is a learning method that can change the atmosphere from being less focused, boring, and boring to being fun and interesting. So that students concentrate on the teaching and learning process. This study aims to determine the application of the Ice breaking method can improve students' understanding of English subjects in telling material in fourth grade at Bilingual Al – A’raf elementary school. The design of this study uses a true experimental design technique using purposive random sampling. One class is the control class and the other is the experimental class. By giving a pretest and posttest. The sample in the study was 26 Bilingual Al – Al – A’raf Elementary School students. implementation research in the even semester of the 2022/2023 academic year. The results of the study show that the application of the Ice breaking method can increase the understanding of Tagged students with the results of the analysis of sig.0.02 <0.05. This means that H0 is rejected and H1 is accepted. There was an increase between the pretest and post-test scores in the experimental class, namely, the results of pretest score of 84.69 while the post-test obtained an average score of 91.07. Thus the research hypothesis is accepted. It can be concluded that the application of ice-breaking has a significant and significant effect on students' understanding of learning.